Phytopharmacology of ashwagandha as an anti-diabetic herb - Kumar V.; Dey A.; Chatterjee S.S. (My University, 2025)
Ashwagandha (Withania somnifera) extracts and several pharmaceutical formulations containing them are currently often used as tonics useful for prevention and cure of mental health problems, including sleep disturbances, accompanying or caused by diverse slowly progressing chronic diseases. The possibility that W. Somnifera could be used for treatments of diabetes and associated metabolic disturbances were first suggested by the results of an exploratory clinical study conducted with its root powdered in diabetic patients and published in 2000. Since then, numerous preclinical and a randomized, double blind and placebo controlled clinical study with extracts of the plant have continued to add experimental evidences in favor of the convictions of the scholars and practitioners of Ayurvedic and other traditionally known systems of medicine that the plant could also be used for prevention and cure of diabetes and other metabolic disorders associated physical and mental health problems. Currently available information suggesting such possibilities are summarized and critically analyzed in this chapter. Potential uses of our current knowledge on phytopharmaclogy and medicinal phytochemistry of the plant and its bioactive constituents for obtaining more sustainable and reproducible health benefits from the plant in patients suffering from, or at risk to, metabolic disorders associated mental health problems, or for discovering novel therapeutic lead against such health problems of the twenty-first century are also discussed. © Springer International Publishing AG 2017. All rights are reserved.